2007
DOI: 10.1016/j.engstruct.2007.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis-oriented stress–strain models for FRP–confined concrete

Abstract: Many stress-strain models have been developed for fibre-reinforced polymer (FRP)-confined concrete. These models fall into two categories: (a) design-oriented models in simple closed-form expressions for direct use in design; and (b) analysis-oriented models in which the stress-strain curve is generated via an incremental process. This paper is concerned with analysis-oriented models, and in particular, those models based on the commonly accepted approach in which a model for actively-confined concrete is used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
269
0
24

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 565 publications
(297 citation statements)
references
References 24 publications
4
269
0
24
Order By: Relevance
“…more than tripled) provided the FRP confinement is strong enough (e.g. Jiang and Teng 2007). The failure of stronglyconfined circular concrete specimens can, however, be explosive and is undesirable in practice.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…more than tripled) provided the FRP confinement is strong enough (e.g. Jiang and Teng 2007). The failure of stronglyconfined circular concrete specimens can, however, be explosive and is undesirable in practice.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Only a small number of studies [10,26,27] reported the FRP properties obtained from ringsplitting tests, and the majority of the studies provided the properties obtained from flat coupon tests or supplied by manufacturers. As for the FRP properties obtained from flat coupon tests, in some of the studies [18,[28][29][30][31][32][33][34][35][36] the elastic moduli (E frp ) and tensile stresses (f frp ) were calculated based on nominal fiber thickness instead of the measured thickness of flat FRP coupons. The datasets from these studies are marked with the superscript 't' in Tables 3 to 7.…”
Section: Eqmentioning
confidence: 99%
“…Average hoop rupture strain reduction factor (k ε ) with FRP type and confinement technique Table 4. Lam and Teng [3] Wu and Zhou [52] Wu and Wang [51] Al-Salloum and Siddiqui [45] Wei and Wu [50] Realfonzo and Napoli [7] Bisby et al [5] Jiang and Teng [32] AAE in predictions of strength enhancement ratio (f' cc /f' co ) Wei and Wu [50] Binici [46] Jiang and Teng [42] Youssef et al [53] Teng et al [49] Fahmy and Wu [47] Teng et al [48] De Lorenzis and Tepfers [4] AAE in predictions of strain enhancement ratio (ε cu /ε co ) …”
mentioning
confidence: 99%
“…Şekil 10(a)'da verilen eğrilere bakıldığında; tek kat CFRP sargılı durumda, C1-I numunesinden elde edilen deneysel (σ − ε) eğrisinin, Jiang ve Teng [10] tarafından önerilen sargılı beton (σ − ε) davranışını ifade eden modelden elde edilen eğriye çok daha yakın olduğu görülmektedir.…”
Section: Cfrp Sargılı Beton Silindir Numunelerden Elde Edilen ( − ) Eunclassified